MEX3A regulates Lgr5+ stem cell maintenance in the developing intestinal epithelium. (13th February 2020) - Pereira, Bruno; Amaral, Ana L; Dias, Alexandre; Mendes, Nuno; Muncan, Vanesa; Silva, Ana R; Thibert, Chantal; Radu, Anca G; David, Leonor; Máximo, Valdemar; van den Brink, Gijs R; Billaud, Marc; et al.
Abstract: Intestinal stem cells (ISCs) fuel the lifelong self‐renewal of the intestinal tract and are paramount for epithelial repair. In this context, the Wnt pathway component LGR5 is the most consensual ISC marker to date. Still, the effort to better understand ISC identity and regulation remains a challenge. We have generated a Mex3a knockout mouse model and show that this RNA‐binding protein is crucial for the maintenance of the Lgr5 + ISC pool, as its absence disrupts epithelial turnover during postnatal development and stereotypical organoid maturation ex vivo . Transcriptomic profiling of intestinal crypts reveals that Mex3a deletion induces the peroxisome proliferator‐activated receptor (PPAR) pathway, along with a decrease in Wnt signalling and loss of the Lgr5 + stem cell signature. Furthermore, we identify PPARγ activity as a molecular intermediate of MEX3A‐mediated regulation. We also show that high PPARγ signalling impairs Lgr5 + ISC function, thus uncovering a new layer of post‐transcriptional regulation that critically contributes to intestinal homeostasis. Synopsis: The RNA‐binding protein MEX3A is expressed at the base of intestinal crypts and is critical for the maintenance of Lgr5 + ISCs during postnatal development. MEX3A regulates the PPARγ pathway, thereby modulating ISC identity and tissue homeostasis. Mex3a −/− mice exhibit growth retardation, postnatal mortality, and a severe impairment of intestinal crypt development. Crypts of Mex3a knockout mice exhibit loss of Lgr5 + intestinal stem cells and disruption of epithelial turnover. Mex3a deletion leads to the aberrant activation of the PPARγ signalling pathway in intestinal crypts. High PPARγ signalling impairs Lgr5 + stem cell function in intestinal organoids. Abstract : The RNA‐binding protein MEX3A is expressed at the base of intestinal crypts and is critical for the maintenance of Lgr5 + ISCs during postnatal development. MEX3A regulates the PPARγ pathway, thereby modulating ISC identity and tissue homeostasis.